Law Enforcement in the Recovery of State Funds from Corruption Crimes - Kartika, Arie; Jaya, Arizon Mega; Zakiran, Asep Hakim; Jastisia, Mentari; Ashady, Suheflihusnaini; Z.S, Edi Mulyadi; Sabatira, Febryani (LAW REFORM, 2024)
Corruption are not adequately addressed by the current legal framework, which fails to provide appropriate sanctions or follow the Constitution in dealing with such crimes. Simply imposing prison sentences is insufficient; efforts must also be made to recover state losses incurred due to corruption. there are still significant constraints in the implementation and enforcement of the law. This study aim to analyze how the applicable laws are enforced to recover financial losses incurred by the state in cases of criminal corruption; and identify the factors inhibiting the effective implementation of laws related to the recovery of these financial losses. This study employs both normative legal methods and empirical research. The research results suggest that to restore the country's economy affected by criminal corruption, it is necessary to undertake measures such as the foreclosure of assets owned by the convicted individuals. Sanctions should include not only monetary compensation equivalent to the value of the assets obtained through corruption but also criminal fines and decisions on the confiscation of goods. One major internal constraint in recovering state finances is the tendency of convicts to opt for prison sentences rather than paying damages as determined by the court.